Prevention and Early Detection of Metabolic Syndrome in Household Community, Surabaya - Ema Qurnianingsih; Lina Lukitasari; Ira Humairah; Siti Khaerunnisa; Gwenny Ichsan Prabowo; Suhartati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction. Metabolic syndrome is a collection of factors believed to increase the risk of atherosclerosis and type 2 diabetes mellitus. The incidence of metabolic syndrome in young adults is increasing, especially in Asian countries. Therefore we need efforts to increase knowledge in society about this disease. Aim. We conducted a socialization program on prevention and early detection of metabolic syndrome in household community to increase public knowledge about this disease.Method. This program was conducted in August 2017 in Wonokromo District, Surabaya. The participants in the activity consisted of 32 people from household community. The activity consisted of blood sampling collection, body weight, and abdominal circumference measurement for risk factor assessment, pre-test, socialization of metabolic syndrome, and post-test.Results. From the results of the pre and post test, we found an increase knowledge of 76.9% participants. The laboratory test results for early detection of metabolic syndrome showed 37.5% of participants had metabolic syndrome. We also found a significant positive correlation between body weight and abdominal circumference (p = 0.000, r = 0.867). There was also a significant negative correlation between body weight and HDL (p = 0.004, r = -0.494), between abdominal circumference and HDL (p <0.05, r = -0.376), and between TG and HDL (p <0.05, r = -4.22).Conclusion. Socialization and early detection of metabolic syndrome can increase knowledge, awareness, and detection of metabolic syndrome in the household community.